2019
DOI: 10.1016/j.yhbeh.2018.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative role of reward in long-term peer and mate relationships in voles

Abstract: In social species, relationships may form between mates, parents and their offspring, and/or social peers. Prairie voles and meadow voles both form selective relationships for familiar same-sex peers, but differ in mating system, allowing comparison of the properties of peer and mate relationships. Prairie vole mate bonds are dopamine-dependent, unlike meadow vole peer relationships, indicating potential differences in the mechanisms and motivation supporting these relationships within and/or across species. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 55 publications
4
54
1
Order By: Relevance
“…Peer relationships themselves are not all the same. For example, they may be selective or non-selective (Lee, 1994 ), transient or enduring (Lidicker and Patton, 1987 ), and motivated or not motivated (Goodwin et al, 2018 ). We sought to characterize and compare the contributions of affiliation, anxiety, and aggression to selective relationships between peers, using monogamous and promiscuous vole species that both form partner preferences for a familiar same-sex peer.…”
Section: Introductionmentioning
confidence: 99%
“…Peer relationships themselves are not all the same. For example, they may be selective or non-selective (Lee, 1994 ), transient or enduring (Lidicker and Patton, 1987 ), and motivated or not motivated (Goodwin et al, 2018 ). We sought to characterize and compare the contributions of affiliation, anxiety, and aggression to selective relationships between peers, using monogamous and promiscuous vole species that both form partner preferences for a familiar same-sex peer.…”
Section: Introductionmentioning
confidence: 99%
“…Long-day housed female meadow voles also sometimes prefer partners over strangers (Ondrasek et al, 2015, Goodwin et al 2018). This may reflect particularly low tolerance of unfamiliar strangers by females in LDs.…”
Section: Meadow Voles: Behaviormentioning
confidence: 99%
“…Assessment of the reward value of social contact, of motivation to work for different social stimuli, and of the role of dopamine in mediating peer relationships in meadow voles will contribute to our understanding of the underlying forces that lead to the specific social preferences that underlie peer relationships. In our initial work on this topic, it appears that peer relationships are not strongly reinforcing for female meadow voles, in that they do not condition place preferences for a cue associated with social housing (Goodwin et al, 2018). We are currently assessing the extent to which meadow and prairie voles will press a lever to gain access to a chamber housing a familiar or unfamiliar conspecific; preliminary findings suggest that female prairie voles work harder to access familiar (vs. unfamiliar) peers or mates, while male prairie voles work harder to access females (vs. males) of any familiarity (S. Lopez and A. Beery, personal communication ).…”
Section: Proximate Factors Influencing Peer Social Behavior In Meadowmentioning
confidence: 99%
“…A recent study demonstrated that female voles that mate, but not those exposed to a peer formed a place preference for cues associated with their mates (Goodwin et al, 2019). The differences between our study and that of Goodwin et al (2019) is that we allowed the females to mate with the male for 6 h in each of the three reinforcing conditioning days. After mating females were returned to their home cage without the male partner.…”
Section: Asexualitymentioning
confidence: 99%
“…administration of estradiol benzoate. In the study of Goodwin et al (2019), females were sexually experienced and had previously produced litters. Futures studies need to address possible rewarding differences between residents and wanderers.…”
Section: Asexualitymentioning
confidence: 99%